Porto Alegre da copa : o mundo dos sonhos de uma cidade imaginada no jornalismo - Pesce, Andressa dos Santos (2017)
This work aims to understand the forms of singularization of Porto Alegre’s imaginary with the arrival of the 2014 FIFA World Cup. Based on the premise that, in Brazil, sport mega-events punctuate the urban narrative and the country's development, the realization of the 2014 World Cup and the 2016 Olympics in brazilian cities becomes a unique moment of urban planning. Cities can reconfigure themselves in terms of representation and imaginary. This resignification also happens from a media look that focuses on the change of status of Porto Alegre, “FIFA host city”", and can reverberate in the urban imaginary in the first decade of the twenty-first century. The World Cup is an opportunity to dream about the city in the media. The journalistic discourse is anchored in the world of everyday life, but it is also a creative source of the dream world. This thesis starts from the following hypothesis: the journalistic discourse builds an imaginary reality for the capital of Rio Grande do Sul with the arrival of the World Cup and triggers the world of dreams. Among the objectives, is the analysis of the transformations that sports mega-events drive in urban strategic development, the understanding of the role of journalism as a technology of the imaginary that works in the symbolic construction of cities and the description of the imaginary of Porto Alegre with the arrival of the World Cup. from the news published five years before the mega-event. The methodology used is the Discourse Analysis, and the corpus is constituted by 29 news reports by Zero Hora’s newspaper, in the capital of the state of Rio Grande do Sul. The year chosen is 2009, when Porto Alegre was confirmed as one of the host cities. In three stages, the analysis proves that the news creates the world of dreams for the city. The subway and the port of the city are pointed like fundamental dreams for the World Cup. The speech about the city with subway uses the description of new services and scenarios for the future, with neighborhoods and streets totally transformed. The real Porto Alegre, without subway, appears problematic, chaotic, while the city without the changes in the port area seems to be subject to the abandonment and the lack of investment. Finally, this thesis concludes that this discourse has as characteristics: persuasion, based on the repetition of the benefits of the World Cup, whose effect may be to induce the public to accept the mega-event, the subway and the dock; the reproduction of the consensus that the support for the World Cup is unanimous and that the changes will bring collective improvements; the standardization effect of the city; and the moralistic content that determines the priority urban works and the steps to be taken in this direction.